A Segregation and Deprotection Approach for Hydrophilic Surfaces Using Amphiphilic Block Copolymers Possessing Polystyrene and Poly[(tri(ethylene glycol) methacrylate)] Segments. Issue 12 (2nd May 2017) - Seki, Akiko; Ishizone, Takashi; Oyane, Ayako; Yokoyama, Hideaki
Abstract : Spontaneously formed hydrophilic polymer brushes composed of poly[(tri(ethylene glycol) methacrylate)] (POH3MA) are fabricated through spontaneous surface segregation of polystyrene‐ block ‐poly[(tri(ethylene glycol) tert ‐butyldimethylsilyl ether methacrylate)] (PS‐ b ‐PSi3MA) in a polystyrene (PS) matrix followed by deprotection of PSi3MA to POH3MA at the PS/water interface. Abstract : This paper fabricates spontaneously formed hydrophilic polymer brushes composed of poly[(tri(ethylene glycol) methacrylate)] (POH3MA) through spontaneous surface segregation of polystyrene‐ block ‐poly[(tri(ethylene glycol) tert ‐butyldimethylsilyl ether methacrylate)] (PS‐ b ‐PSi3MA) in a polystyrene (PS) matrix followed by deprotection of PSi3MA to POH3MA at the PS/water interface. When protected, the tert ‐butyl‐terminated hydrophilic PSi3MA blocks segregate at the air or vacuum surface at elevated temperatures. The surface‐segregated structures can be fixed by cooling to room temperature followed by deprotection of the PSi3MA groups to provide surfaces fully covered by unprotected POH3MA, with OH groups on glassy robust PS. Such hydrophilic POH3MA brushes prevent the adsorption of human serum albumin and are expected to be useful in antifouling surfaces.